(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article notes that the large-scale economic reforms implemented in Uzbekistan in recent years have led to an intensification of investment processes. In the current economy, the establishment of new industries and sectors, the expansion of existing production capacity, the creation of jobs require the attraction of more funds and resources.